Pathogenic E. coli from Cattle as a Reservoir of Resistance Genes to Various Groups of Antibiotics - Alexandra Tabaran; Virginie Soulageon; Flore Chirila; Oana Lucia Reget; Marian Mihaiu; Mihai Borzan; Sorin Daniel Dan (MDPI AG, 2022)
Antimicrobial resistance has become a worldwide concern in all public health domains and reducing the spread has become a global priority. Pathogenic E. coli is responsible for a number of illnesses in humans and outbreaks in the past have been correlated with the consumption of contaminated bovine products. This is why surveillance in all the steps of production is essential. This study focused on identifying the pathogenic strains of E. coli in two large bovine abattoirs from Romania and France, and on associating them with the antimicrobial resistance patterns. A total of 250 samples from intestinal content were aseptically collected during the evisceration step of the cattle slaughtering process, from which 242 E. coli strains were isolated. Seventeen percent of all samples tested positive to at least one E. coli isolate carrying eaeA, stx1 and stx2 genes. The most prevalent genetic profile found in the E. coli strains tested was Stx1-positive and Stx2/eaeA-negative. More than 68% of the pathogenic E. coli isolated in Romania showed multi-drug resistance (MDR) and in France, the percentage was significantly lower (38%). The MDR profiles showed a high gene diversity for antibiotic resistance, which represents a great risk for environmental spread and human health. Our results indicate that in Romania, bovines can represent a reservoir for MDR E. coli and, hence, a surveillance system for antimicrobials usage in farm animals is highly needed.